PENGARUH DEVIDEND PER SHARE (DPS) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM PADA PERUSAHAAN INDEKS LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Sri Intan Purnama; Muhamad Nur (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2020)
This study aims to determine the effect of Devidend Per Share (DPS) And Return On Equity (ROE) Against Stock Price. This research use sample Company Indeks LQ45 year 2010-2016 Devidend Per Share (DPS), Return On Equity (ROE) and Stock Price are measured by looking at the financial statements of companies that are listed on the Indonesia Stock Exchange (IDX) for 2010-2016 period.Population in this research as many as 45 companies that listed in Indonesia Stock Exchange (IDX) period 2010-2016. After the selection by Purposive Sampling method in the population, there are 11 companies Indeks LQ45 used as sample. This research uses quantitative method with descriptive approach to know influence between Devidend Per Share (DPS) and Return On Equity (ROE) to Stock Price. Using secondary data and data analysis technique using multiple regression analysis.Based on the results of the study, Devidend Per Share (DPS) has a positive and significant effect on Stock Prices of Indeks LQ45 companies listed in Indonesia Stock Exchange (IDX) year 2010-2016.with positive regression coefficient and t value of 8,342 significant 0,000. And Return On Equity (ROE) have positive and significant effect to stock price of company Indeks LQ45 which listed in Indonesia Stock Exchange (IDX) year 2010-2016 with result of positive regression coefficient value and t value 4,337 significant 0,000.